Oh, let's paint a happy little math problem here! First, we start by solving the exponent: 1 to the power of 3 is 1. Then we move on to multiplication: 2 times 1 is 2. Finally, we divide 6 by 2, which gives us 3. So, the answer to 6 divided by 2 multiplied by 1 to the third power minus 2 is 3.
2X -1/3 * 2X3 - X 1/3 Order of operation; multiply first. ( multiply coefficients, add exponents ) 4X 8/3 - X 1/3 3X 7/3 =====
simplified it would equal: 24x to the third power - x to the second power - x to the sixth power - 34
To multiply by 10 to a negative power just move the decimal point that number of spaces to the left: 2.0 x 10 to the minus 3 = 0.002
-8
x cubed minus 216
10,077,692.
2X -1/3 * 2X3 - X 1/3 Order of operation; multiply first. ( multiply coefficients, add exponents ) 4X 8/3 - X 1/3 3X 7/3 =====
Multiply by three.
Expressing a number to the "third power" means to multiply that number by itself three times. Multiply 329313.6 times 329313.6, and then multiply that answer by 329313.6. The resulting answer is the third power [329313.63].
simplified it would equal: 24x to the third power - x to the second power - x to the sixth power - 34
To multiply by 10 to a negative power just move the decimal point that number of spaces to the left: 2.0 x 10 to the minus 3 = 0.002
-8
1
x cubed minus 216
Yes.
14x squared minus 7x to the 3rd power can be factored to 7x2(2-x).
(4x - 3y)(16x^2 + 12xy + 9y^2)